A Bedtime for Bear - Becker, Bonny; Illustratrated by Denton, Kady MacDonald (London Walker Books, 2010)
A small but effervescent overnight guest tries the patience of a curmudgeonly bear who needs absolute quiet to fall asleep.
Include Color Illustrations
Keywords: Bedtime -- Juvenile fiction -- Sleepovers -- Juvenile fiction -- Bears -- Juvenile fiction